EVALUASI KARAKTERISTIK KUALITAS AIR DANAU LIMBOTO - Fitryane Lihawa; Marike Mahmud (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
This research aims at evaluating water-quality characteristics in Limboto Lake ecosystem in accordance with its designation. The research took place in Limboto Lake and the rivers that drain water into the lake. Samples were taken at 5 spots in Limboto Lake and 8 spots at the surrounding rivers. The rivers that flow into Limboto Lake and were made as samples consisted of Alo River (3 samples), Toyidito River (2 samples), Molamahu River (1 sample), Molalahu River (1 sample) and also Alopohu Dam (1 sample). Instruments used were pH meter and thermometer for physical parameters, and AAS for chemical parameters. Microbiology was measured using MPN method. The results of the analysis indicated that the water quality in Limboto Lake and the surrounding rivers were polluted. The parameters of nitrate, phosphate and hydrogen sulfide were above the standard stipulated by the Government Regulation Number 82 of 2001.